Health service utilization by indigenous cancer patients in Queensland: a descriptive study - Bernardes Christina M; Whop Lisa J; Garvey Gail; Valery Patricia C (BMC, 2012)
Abstract Introduction Indigenous Australians experience more aggressive cancers and higher cancer mortality rates than other Australians. Cancer patients undergoing treatment are likely to access health services (e.g. social worker, cancer helpline, pain management services). To date Indigenous cancer patients' use of these services is limited. This paper describes the use of health services by Indigenous cancer patients. Methods Indigenous cancer patients receiving treatment were recruited at four major Queensland public hospitals (Royal Brisbane Women's Hospital, Princess Alexandra, Cairns Base Hospital and Townsville Hospital). Participants were invited to complete a structured questionnaire during a face-to-face interview which sought information about their use of community and allied health services. Results Of the 157 patients interviewed most were women (54.1%), of Aboriginal descent (73.9%), lived outer regional areas (40.1%) and had a mean age of 52.2 years. The most frequent cancer types were breast cancer (22.3%), blood related (14.0%), lung (12.1%) and gastroenterological (10.8%). More than half of the participants reported using at least one of the 'Indigenous Health Worker/Services' (76.4%), 'Allied Health Workers/Services' (72.6%) and 'Information Sources' (70.7%). Younger participants 19-39 years were more likely to use information sources (81.0%) than older participants who more commonly used community services (48.8%). The cancer patients used a median of three health services groups while receiving cancer treatment. Conclusions Indigenous cancer patients used a range of health services whilst receiving treatment. Indigenous Health Workers/Services and Allied Health Workers/Services were the most commonly used services. However, there is a need for further systematic investigation into the health service utilization by Indigenous cancer patients.